한강수계 내 Melamine 농도검출과 GAC처리에서의 파과모델링 - 이상중(Sang Jung Lee); 이재엽(Jai Yeop Lee); 한인섭(Ihn Sup Han) (Daehan hwan'gyeong gonghag hoeji, 2011)
Currently, melamine is being used variously in our lives such as resins, flame retardants, adhesive, laminate etc. And understandably sewer of stream of wastewater containing Melamine has also increased. GHS (Globally Harmonized System of Classification and Labelling of Chemicals) of EU safety guidelines says that it can cause cancer. Still, study on toxicity of Melamine is going on. In this research, melamine contamination level of the Han River and River Basin was analyzed by HPLC/UV. And the experiments of GAC adsorption were conducted and the model was studied. We collected the 3 same samples at the suburbs of Paldang Dam located in the relative upstream in Han River and Ttukseom amusement park, the downstream region and collected samples equally at the Hongreung stream, Wangsuk stream, Cheonggye stream among streams flowing into Han River and then measured Melamine concentration after purification. As a result, melamine was not detected at the suburbs of Paldang Dam and it was detected at Ttukseom amusement park, the downstream of it, in the concentration of $0.312μg/L$. The Wangsuk stream with $0.578μg/L$ highest Cheonggye stream and Hongreung stream was detected with each $0.197μg/L$ and $0.325μg/L$. Although the concentration was low in general, melamine detection could be checked at most point. In 1970, the world capacity of Melamine was estimated at 200,000 ton, with current production estimated to be 1,400,000 ton. Melamine of Han River and rivers flowing into Han River is present at low concentration but pollution will increase in the future due to increase of use. Depending on the size of activated carbon in the experiment were slightly different. But the breakthrough model is almost identical. 현재, melamine은 레진, 내화제, 접착제, 라미네이트 등 우리 생활에 다양하게 사용되고 있다. 그로 인해 melamine이 포함된 폐수의 수계 유입 또한 증가하고 있다. EU안전지침서의 GHS에는 melamine을 암 유발 가능성이 있는 물질로 구분하고 있다. 하지만 아직까지 melamine에 대한 독성연구는 진행 중이며 어떤 영향을 주는지 아직까지 밝혀진 사실이 적다. 본 연구에서는 한강과 주변하천의 melamine 오염 정도를 HPLC/UV를 이용하여 오염 정도를 파악하였다. 그리고 활성탄을 이용한 흡착실험 및 모델링에 관한 연구를 하였다. 우선 한강수계 중 상대적으로 상류에 있는 팔당댐 근교와 그보다 하류지역인 뚝섬유원지에서 동일한 시료를 3개씩 채수하였고 한강에 유입되는 하천 중 홍릉천, 왕숙천, 청계천에서 동일하게 시료를 채수하여 정제 후 melamine 농도를 측정하였다. 그 결과 팔당댐 근교의 시료에서는 melamine이 검출되지 않았으며 그보다 상대적으로 하류인 뚝섬유원지에서는 $0.312μg/L$농도가 검출되었다. 왕숙천에는 $0.578μg/L$로 가장 높았으며 청계천과 홍릉천은 각 $0.197μg/L$, $0.325μg/L$로 검출되었다. 전체적으로 낮은 농도지만 대부분의 지점에서 melamine의 검출을 확인할 수 있었다. 1970년대에는 melamine 생산량이 200,000 ton에서 최근에는 1,400,000 ton으로 계속적인 사용의 증가로 수계오염은 심화될 것으로 보인다. 활성탄을 이용한 흡착 실험에서는 활성탄 크기에 따라 melamine흡착에 약간의 차이를 보였으나 파과모델과 어느 정도 일치함을 보였다.